Measurements of an elliptic pipe jet - Khaw, Boon Hong (2019)
This study presents the flow development of a jet with a 999mm long smooth fiberglass pipe and an elliptic nozzle exit with major and minor axis length of 50mm by 25mm respectively. The objective of this study is to investigate the flow fields of an elliptic pipe jet and carry out comparison to an elliptic contraction jet to explore possible correlations. Velocity measurements within the flow fields were taken using single hot wire probe positioned at different stream-wise locations (x-axis) for the major (y) and minor (z) axes. For all velocity measurements, the jet exit velocity is kept steady at 24.0 ± 0.5 m/s resulting in a Reynolds number of about 55500. The 999mm long smooth fiberglass pipe enables discharge of fully developed turbulent pipe flow at the nozzle exit for the major axis. In this study, documentation of the mean velocity profiles and contributing fluctuation elements were made. The momentum thickness of the minor axis was discovered to be thinner than the major axis. The length of the potential core was determined to be approximately x/De of 4. The near-field region exhibits distinctive degree of self-preservation whereas full self-preservation was observed in the far-field region at x/De of 9 and 7 for the major and minor axes respectively. The jet spreading rate for the minor axis was found to be greater than the major axis which led to axis switching occurring at x/De of 13.5. Linear regression was deemed to be suitable to represent the jet spreading rate and mean centerline velocity decay rate.